Bonsoir,
1) [tex](d_1):x=-4\\\\(d_2):y=\dfrac{1}{2}x+2\\\\(d_3):y=-3x+4\\\\(d_4):y=-3[/tex]
2) a) Résoudre le système :
[tex]\left\{\begin{matrix}y=\dfrac{1}{2}x+2\\ y=-3x+4\end{matrix}\right.\\\\\dfrac{1}{2}x+2=-3x+4\\\\\dfrac{1}{2}x+3x=4-2\\\\\dfrac{1}{2}x+\dfrac{6}{2}x=2\\\\\dfrac{7}{2}x=2\\\\x=2\times\dfrac{2}{7}\\\\x=\dfrac{4}{7}\approx 0,57[/tex]
[tex]y=-3\times\dfrac{4}{7}+4\\\\y=-\dfrac{12}{7}+4\\\\y=-\dfrac{12}{7}+\dfrac{28}{7}\\\\y=\dfrac{16}{7}\approx2,29[/tex]
Donc [tex]A(\dfrac{4}{7};\dfrac{16}{7})[/tex].
b) Graphiquement, on pourrait lire : A(0,6 ; 2,3)
3) Résoudre le système :
[tex]\left\{\begin{matrix}y=-3x+4\\ y=-3\end{matrix}\right.\\\\-3x+4=-3\\\\-3x=-3-4\\\\-3x=-7\\\\x=\dfrac{-7}{-3}\\\\x=\dfrac{7}{3}\approx2,3\\\\y=-3[/tex]
Donc [tex]D(\dfrac{7}{3};-3)[/tex]